Distinction of Sacredness and Economic Commodification in Bau Nyale Tradition in Lombok Society - Hanik, Umi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
Bau Nyale is a Lombok Sasak tradition associated with Princess Mandalika's sacred and mythological qualities. Every year, this ritual is carried out as a manner of thanking Allah and honoring Princess Mandalika's sacrifice in preserving West Nusa Tenggara's integrity. This study aims to explain the distinction between sacredness and economic commodification in the Bau Nyale tradition. The research method used is qualitative, with a sociological approach to religion. The main informants in this study were forty people from elements of the Chief of Tribal Council, Tourism Operators, Religious Leaders, Village Youth, Village Apparatus, Economic Actors/ Traders, Participants/ Community who joined Bau Nyale, who were selected by purposive sampling technique. The research procedure was carried out in stages: data collection, reduction, presentation, and analysis. This study shows that the distinction between sacredness and economic commodification in the Bau Nyale tradition is seen in the socio-religious and cosmological form of the Sasak people of Lombok, which has an interpretation value between the society and tourism managers. Bau Nyale is a symbol of the success of the feast and a form of gratitude to God for the abundance of grace and gifts to the harvest, both in the agricultural and marine fields. The mythology of Princess Mandalika as a figure of wisdom represents the dignity and worth of the female figure of the Sasak people of Lombok. In addition, the Bau Nyale tradition has a tourism value that should be promoted to be known in foreign countries, aimed at boosting the economy of Lombok, West Nusa Tenggara.